Catalytic Biosensors Operating under Quasi‐Equilibrium Conditions for Mitigating the Changes in Substrate Diffusion. Issue 52 (23rd November 2022) - Muhs, Anna; Bobrowski, Tim; Lielpētere, Anna; Schuhmann, Wolfgang
Abstract: Despite the success of continuous glucose measuring systems operating through the skin for about 14 days, long‐term implantable biosensors are facing challenges caused by the foreign‐body reaction. We present a conceptually new strategy using catalytic enzyme‐based biosensors based on a measuring sequence leading to minimum disturbance of the substrate equilibrium concentration by controlling the sensor between "on" and "off" state combined with short potentiometric data acquisition. It is required that the enzyme activity can be completely switched off and no parasitic side reactions allow substrate turnover. This is achieved by using an O2 ‐independent FAD‐dependent glucose dehydrogenase embedded within a crosslinked redox polymer. A short measuring interval allows the glucose concentration equilibrium to be restored quickly which enables the biosensor to operate under quasi‐equilibrium conditions. Abstract : We propose a catalytic quasi‐equilibrium biosensor concept in which an O2 ‐insensitive enzyme is wired with a redox polymer to the electrode. This allows the enzymatic conversion to be switched off by applying a low potential, the redox polymer can be charged with a short positive potential pulse, and the glucose concentration can be determined potentiometrically with minimal disturbance of the concentration equilibrium. This concept is opening the door for mitigating any impact of the foreign‐body reaction in implantable biosensors.